Exploring the correlates of frequency of Tai Chi Chuan participation among Chinese adults in an urban context - Chao, Yizhen; Wang, Yaqing; Yu, Yongtao (Frontiers in Psychology, 2025)
BackgroundTai Chi Chuan (TCC) has achieved global recognition and was inscribed on the UNESCO Representative List of Intangible Cultural Heritage of Humanity in 2020. However, a significant gap remains in research examining the correlates of TCC participation. This study aims to address this gap by analyzing data from a sample of adult TCC practitioners in urban parks in Zhengzhou City.MethodsThis study collected data from 998 Chinese adults practicing TCC in public parks in Zhengzhou City, Henan Province, using face-to-face questionnaire interviews. Data analysis involved descriptive statistics, univariate analysis, and backward stepwise ordinal regression modeling.ResultsTwelve independent variables were found to be significantly associated with the frequency of TCC participation: age, mental problems, health problems, investment, alternate spaces, distance, awards, health motivation, partners, gender, nature of labor, and migration. The remaining variables showed no significant association with participation frequency.ConclusionThis study identified key determinants influencing the frequency of TCC participation among Chinese adults. The research findings provide important evidence for developing intervention strategies aimed at increasing participation frequency.